Effect of modified balanced cupping therapy based on Traditional Chinese Medicine meridian theory combined with head scraping in the treatment of wind-cold type cold (中医经络平衡火罐改良法联合头部刮痧治疗风寒感冒的效果观察) - YANG Jing (杨晶); WU Ying (伍颖) (中西医结合护理, 2024)
Objective To observed the effect of modified balanced cupping therapy based on Traditional Chinese Medicine meridian theory combined with head scraping in the treatment of wind-cold type cold. Methods Totally 30 patients with wind-cold type cold were included as research objects. They were treated with modified balanced cupping therapy based on Traditional Chinese Medicine meridian theory combined with head scraping, and the changes of symptoms and signs of cold before and after treatment were observed. Results Among the 30 patients, 17 cases were cured after one treatment course, 5 cases were cured after two treatment courses and 2 cases were cured after three treatment courses. The total cure rate was 80. 00%. Conclusion modified balanced cupping therapy based on Traditional Chinese Medicine meridian theory combined with head scraping can effectively treat wind-cold cold. (目的 观察中医经络平衡火罐改良法联合头部刮痧治疗风寒感冒的效果。方法 选取2023年9月—12月收治的风寒型感冒患者30例, 使用中医经络平衡火罐改良法联合头部刮痧治疗, 观察其感冒症状体征变化情况。结果 30例患者中经治疗1次治愈者17例, 2次治愈者5例, 3次治愈者2例, 总治愈率80. 00%。结论 中医经络平衡火罐改良法联合头部刮痧能有效的治疗风寒感冒。)